2018
DOI: 10.1002/jms.4071
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray mass spectrometry and molecular modeling study of formation and stability of silver complexes with diazaperylene and bisisoquinoline

Abstract: The complex formation of the following diazaperylene ligands (L) 1,12-diazaperylene 1, 1,1'-bisisoquinoline 2, 2,11-disubstituted 1,12-diazaperylenes (alkyl = methyl, ethyl, isopropyl, 3, 5, 7), 3,3'-disubstituted 1,1'-bisisoquinoline (alkyl = methyl, ethyl, isopropyl, 4, 6, 8 and with R = phenyl, 11 and with pyridine 12), and the 5,8-dimethoxy-substituted diazaperylene 9, 6,6'-dimethoxy-substituted bisisoquinoline 10 with AgBF4 was investigated. Collision-induced dissociation measurements were used to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 64 publications
(104 reference statements)
0
3
0
Order By: Relevance
“…Electrospray MS studies of methanol solutions containing Ag(BF 4 ) and biiq exhibited ions assigned to the species [Ag(biiq) 2 ] + and [Ag(biiq)] + ; if bpy (1) or phen (2) were also in the solution the ions [Ag(biiq)(1)] + and [Ag(biiq)(2)] + were observed [126]. Subsequent studies together with DFT level calculations were reported for substituted biiq ligands [85].…”
Section: Groupmentioning
confidence: 95%
See 1 more Smart Citation
“…Electrospray MS studies of methanol solutions containing Ag(BF 4 ) and biiq exhibited ions assigned to the species [Ag(biiq) 2 ] + and [Ag(biiq)] + ; if bpy (1) or phen (2) were also in the solution the ions [Ag(biiq)(1)] + and [Ag(biiq)(2)] + were observed [126]. Subsequent studies together with DFT level calculations were reported for substituted biiq ligands [85].…”
Section: Groupmentioning
confidence: 95%
“…The complexes [{Ag(µ-biiq)} n ]X (X = BF 4 or CF 3 SO 3 )•H 2 O are one-dimensional polymers; the solid-state structure of [{Ag(µ-biiq-1κN,2κN')} n ](CF 3 SO 3 ) n •nH 2 O (CSD Refcode YAQSEQ, space group C2/c, N2-C1-C1 -N2 torsion angle 111.76 • , Figure17c) has been reported[148].Electrospray MS studies of methanol solutions containing Ag(BF 4 ) and biiq exhibited ions assigned to the species [Ag(biiq) 2 ] + and [Ag(biiq)] + ; if bpy (1) or phen(2) were also in the solution the ions [Ag(biiq)(1)] + and [Ag(biiq)(2)] + were observed[126]. Subsequent studies together with DFT level calculations were reported for substituted biiq ligands[85].The preferred geometry for gold(I) is linear two-coordinate and the biiq ligand cannot, therefore, coordinate in a chelating bidentate mode. Two types of discrete complexes are found with gold(I) centers.…”
mentioning
confidence: 99%
“…The N-substitution can be used for fine-tuning the optical properties [15]. The complex formation of dap with transition metal ions (Fe, Co, Ni, Cu, Zn, Ru, Os, Re, Pd, Pt, Ag, Cd) in the gas phase has been studied by electrospray ionization mass spectrometry [16,17]. Heteroleptic polymetallic Ag(I) and Cu(I) complexes were obtained and a multidentate ligand containing a large N,P,N,P,N core yielding interesting structures with π-π stacked columns or discrete sixfold stacks [18].…”
Section: Commentmentioning
confidence: 99%